Vaccines for bovine neosporosis: current status and key aspects for development. (7th July 2016) - Horcajo, P.; Regidor‐Cerrillo, J.; Aguado‐Martínez, A.; Hemphill, A.; Ortega‐Mora, L. M.
Summary: Bovine neosporosis is a worldwide concern due to its global distribution and great economic impact. Reproductive failure in cattle due to abortion leads to major economic losses associated with the disease. Currently, there is no treatment or vaccine available against abortion or transmission caused by Neospora caninum infection in cattle. However, vaccination is considered the best measure of control against bovine neosporosis. Several host and parasite factors can influence the dynamics of the infection in bovines. Moreover, the availability of well‐defined infection models is a key factor for the evaluation of vaccine candidates. However, working with cattle is not easy due to difficult handling, facilities and costs, and therefore, 'more affordable' models could be used for screening of promising vaccines to establish proof of concept. So far, live‐attenuated vaccines have shown good efficacy against exogenous transplacental transmission; however, they have relevant disadvantages and associated risks, which render inactivated or subunit vaccines the best way forward. The identification of novel potential targets and vaccines, and the application of innovative vaccine technologies in harmonized experimental animal models, will accelerate the development of an effective vaccine against bovine neosporosis.